Ammonia gas sensing properties at low temperatures of nanocomposites of graphene oxide and tungsten oxide nanobricks - Tu, Nguyen Cong; Kiet, Nguyen Anh; Minh, Phung Nhat; Dinh, Ngo Xuan; Tuan, Le Anh; Anh, Luu Thi Lan; Tho, Do Duc; Lam, Nguyen Huu (Vietnam Journal of Science and Technology, 2020)
Nanocomposites of graphene oxide (GO) and tungsten oxide (WO3) nanobricks are synthesized by co-dispersing graphene oxide and tungsten oxide nanobricks in bi-distilled water with different weight ratios (0.1, 0.3 and 0.5 wt.% of graphene oxide). The ammonia gas sensing properties of nanocomposites are studied at low temperatures range (50, 100 and 150 oC) with the static gas-testing system. The co-appearance and the strong interaction between graphene oxide and tungsten oxide in the nanocomposite are confirmed by Raman scattering analysis. The content of GO in nanocomposite strongly affects the resistance of nanocomposite-based sensors. When the working temperature increase from 50 oC to 150 oC, the response of sensors switches from the p-type (at 50 oC) to n-type (at 150 oC) behavior. At 150 oC, the nanocomposite-based sensors show the most stable ammonia gas sensing characteristics. The working resistance of the pristine WO3 sensor reduced from 1.35 MΩ to 90, 72 and 27 kΩ when compositing with 0.1, 0.3 and 0.5 wt.% GO at 150 oC, respectively. The 0.5 wt.% GO/WO3 -based sensor shows low response but with low working resistance, shorter response and recovery times (20 s and 280 s, respectively) which is promising for low power-consumption gas sensors.